2006
DOI: 10.1074/jbc.m511785200
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of GTP with the ATP-grasp Domain of GTP-specific Succinyl-CoA Synthetase

Abstract: Two isoforms of succinyl-CoA synthetase exist in mammals, one specific for ATP and the other for GTP. The GTP-specific form of pig succinyl-CoA synthetase has been crystallized in the presence of GTP and the structure determined to 2.1 Å resolution. GTP is bound in the ATP-grasp domain, where interactions of the guanine base with a glutamine residue (Gln-20␤) and with backbone atoms provide the specificity. The ␥-phosphate interacts with the side chain of an arginine residue (Arg-54␤) and with backbone amide n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
54
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 58 publications
3
54
1
Order By: Relevance
“…To gain insight into the potential binding mode of Gua nucleotides, we superimposed ckcACD1 with the ATP-grasp domain containing enzyme CK2 from Zea mays, which is known to metabolize Ade and Gua nucleotides (42)(43)(44). We found that (i) the Ade moiety of ATP bound to CK2 [Protein Data Bank (PDB) ID code 1DAW] is oriented comparable to ckcACD1 and (ii) the Gua moiety of GTP bound to CK2 (PDB ID code 1DAY) is shifted in its position and compares quite well with the binding mode found in the structure of GTP-specific ssSCS (16). Hence, we expect a comparable binding mode for Guo nucleotides in ckcACD1.…”
Section: Ckcacd1 and Ecscs Display Very Similar Features For The Catasupporting
confidence: 53%
See 2 more Smart Citations
“…To gain insight into the potential binding mode of Gua nucleotides, we superimposed ckcACD1 with the ATP-grasp domain containing enzyme CK2 from Zea mays, which is known to metabolize Ade and Gua nucleotides (42)(43)(44). We found that (i) the Ade moiety of ATP bound to CK2 [Protein Data Bank (PDB) ID code 1DAW] is oriented comparable to ckcACD1 and (ii) the Gua moiety of GTP bound to CK2 (PDB ID code 1DAY) is shifted in its position and compares quite well with the binding mode found in the structure of GTP-specific ssSCS (16). Hence, we expect a comparable binding mode for Guo nucleotides in ckcACD1.…”
Section: Ckcacd1 and Ecscs Display Very Similar Features For The Catasupporting
confidence: 53%
“…At the corresponding sequence position, other members of the ACD family feature either Arg or Lys residues. In the case of GTP bound to ssSCS, the amino function of the side chain of Lys222β interacts with the gamma-phosphate in a similar manner (16), which might indicate a specific role for this residue.…”
Section: Binding Mode Of Ado Nucleotides Within Site II Located In Thmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been pointed out that other members in this superfamily also commonly harbor these five domains, although the order and distribution of the domains between the two subunits display variation (18). Although all previously characterized classical SCSs share the same subunit and domain structure (domain order: ␣-subunit, 1-2; and ␤-subunit, 3-4-5) (23,24,27,28), the SCS identified here from T. kodakaraensis exhibits a distinct structure: domain 5 is fused to the ␣-subunit (␣-subunit, domains 1-2-5; and ␤-subunit, domains 3-4) (Fig. 2).…”
Section: Identification Of An Scs In Cell-free Extracts Of Tmentioning
confidence: 99%
“…ADP/GDP-forming succinyl-CoA synthetase (SCS) also belongs to this superfamily and catalyzes the reversible conver-sion of succinyl-CoA to succinate and CoA concomitant with substrate level phosphorylation of ADP/GDP (23,24). Generally, SCS functions in the tricarboxylic acid cycle of aerobic organisms, and it has been suggested that the mammalian ATPdependent enzyme serves a catabolic role, whereas the GTPdependent enzyme is involved in succinyl-CoA synthesis (24). Many Archaea also possess closely related homologs of SCS on their genomes.…”
mentioning
confidence: 99%